POTENCY OF DEVELOPMENT GRAPTOPHYLLUM AS ONE OF INDONESIAN ORIGINAL HERBS; A BIBLIOMETRIC STUDY - Feda Anisah Makkiyah (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2022)
Indonesia is home to thousands of herbal medicine, and one of the species that would gain more popularity is the Graptophyllum species. This indigenous Papua island plant grows as a shrub plant in the garden of many houses. This study aims to map the research available about this species and explore the potential effects of this plant. Methods. The bibliometric study was performed to map the articles. Scopus databases and Vosviewer were used in this study. Results. 53 articles were withdrawn from Scopus databases. Indonesia has the highest number of publications and many Indonesian researchers collaborated with authors from Japan, Switzerland, and Sweden. The keywords were divided into three clusters and most of the composition discussed was flavonoid. The species discussed was the Graptophyllum pictum. Conclusion. As one of the Indonesian herbal medicine, Graptophyllum pictum is more popular in its own country. Hopefully, the development of chemical drugs from Graptophyllum pictum will be in its own country.